2017
DOI: 10.3233/jad-160913
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of Blood Serums from Alzheimer’s Disease Patients Using iTRAQ Labeling Technology

Abstract: Alzheimer' disease (AD) is the most common form of dementia affecting up to 6% of the population over the age of 65. In order to discover differentially expressed proteins that might serve as potential biomarkers, the serums from AD patients and healthy controls were compared and analyzed using the proteomics approach of isobaric tagging for relative and absolute quantitation (iTRAQ). For the first time, AD biomarkers in serums are investigated in the Han Chinese population using iTRAQ labeled proteomics strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 83 publications
8
49
0
3
Order By: Relevance
“…The iTRAQ analysis was performed according to the previous study . Plasma proteins (100 μg) were reduced, alkylated, and digested with trypsin (Promega, Madison, WI, USA) at a ratio of 1:30 at 37 °C for overnight, and then labeled with the iTRAQ reagents (AB Sciex, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The iTRAQ analysis was performed according to the previous study . Plasma proteins (100 μg) were reduced, alkylated, and digested with trypsin (Promega, Madison, WI, USA) at a ratio of 1:30 at 37 °C for overnight, and then labeled with the iTRAQ reagents (AB Sciex, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The dried samples were reconstituted in 100 μL double‐distilled water and injected into the Agilent HPLC (HPLC; Agilent Technologies, Santa Clara, CA, USA) with a high pH RP column (Durashell, C18, 250 mm × 4.6 mm, 5 μm; Bonna‐Agela Technologies, Inc., Wilmington, DE, USA). Peptides were eluted and combined into 10 groups and lyophilized and stored at −80 °C …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have used proteomics approaches to discover biomarkers for AD [46]. Russell et al combined tissue and fluid proteomics with tandem mass tags (TMT) for detection of low-abundance peptides in biological fluids [7].…”
Section: Introductionmentioning
confidence: 99%
“…Curiously, treatment of astrocytes with resveratrol alone significantly increased TSP1 mRNA levels (29), whereas others have found that b-amyloid inhibits TSP1 release from astrocytes (200). These findings may be relevant to the accumulating evidence linking the neurodegenerative condition, Alzheimer's disease and TSP1 (19,200,232). Further studies employing exogenous ROS and gene silencing of ROS enzymatic sources would be useful to evaluate possible ROS-stimulated feed-forward induction of TSP1.…”
Section: Tsp1 and Ros Signaling In Vivomentioning
confidence: 94%